2020
DOI: 10.1002/jssc.201901148
|View full text |Cite
|
Sign up to set email alerts
|

Determination of personal care products in water using UHPLC–MS after solid phase extraction with mesoporous silica‐based MCM‐41 functionalized with cyanopropyl groups

Abstract: A silica-based MCM-41 mesoporous material functionalized with cyanopropyl groups has been synthesized by cocondensation, characterized and applied to preconcentrate six parabens and three UV filters in river and swimming-pool waters. The analytes were quantified by ultra-high performance liquid chromatography-tandem mass spectrometry, according to the Directive 96/23/EC. Even though matrix effect was negligible, quantification in river water samples with the standard addition approach improved the recoveries o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Most of the studies reported in this review used the SPE procedure, sometimes modified according to the chemical structure of the UVF to be determined [45,51,52,56,60,61,69,70]. Other authors developed alternative extraction techniques using a semipermeable membrane device for the simultaneous extraction of different UVF classes [49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies reported in this review used the SPE procedure, sometimes modified according to the chemical structure of the UVF to be determined [45,51,52,56,60,61,69,70]. Other authors developed alternative extraction techniques using a semipermeable membrane device for the simultaneous extraction of different UVF classes [49].…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of organic UVFs in investigated matrices, chromatographic separation was generally performed on reverse phase C18 columns, except for two studies that used a C8 column [51,60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the overall good characteristics, the method was time-consuming, given that 100-200 mL of sample was passed with a flow rate of 5 mL/min (20–40 min extraction time), plus 30 min of solvent evaporation was required [ 66 ]. Kharbouche et al proposed the use of mesoporous silica-based materials MCM-41 and MCM-41-CN(a cyanopropyl derivatized MCM-41) as SPE sorbents, for the extraction of four BPs [ 67 ]. They optimized the parameters of the method and found that the optimum pH for MCM-41 was 6.0 and for MCM-41-CN was 3.5.…”
Section: Sample Preparation For Benzophenone Detectionmentioning
confidence: 99%
“…The intra-day precisions of the method were between 6.0 and 15.5 (spiked with 0.1 ng/L BPs) and from 8.2 to 10.8 (spiked with 0.5 ng/L). This hints towards a rather irreproducible method [ 67 ]. Likewise, Sun et al proposed an extraction method using molecularly imprinted polymers as SPE sorbents, for the analysis of tap water and river water [ 68 ].…”
Section: Sample Preparation For Benzophenone Detectionmentioning
confidence: 99%